2021
DOI: 10.1111/geb.13241
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and phenology of the jellyfish Rhizostoma pulmo (Cnidaria: Scyphozoa) in southern European seas

Abstract: Aim Global anthropogenic changes have altered biogeography and phenology of marine populations, thereby promoting a spatial reconfiguration in the functioning of marine ecosystems. Among these changes, massive proliferations of jellyfish in temperate latitudes warn of potential alterations in biogeochemical fluxes, ecosystems’ structure and assets, and the services they provide to human welfare. Understanding driving factors shaping large‐scale patterns of jellyfish proliferations is a pressing need in global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 67 publications
4
25
0
Order By: Relevance
“…In the Ligurian Sea, P. noctiluca has been reported as present along most of the coastline but exhibiting alternating years of presence and absence [3,28], in full agreement with data collected in the current study. Regarding R. pulmo, the general distribution pattern shown in the present study is consistent with that reported by Boero et al [15] and Leoni et al [93]. For P. noctiluca, one of the environmental variables with highest importance was salinity, which is in agreement with Piccinetti Manfrin and Piccinetti [94] and Canepa et al [30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the Ligurian Sea, P. noctiluca has been reported as present along most of the coastline but exhibiting alternating years of presence and absence [3,28], in full agreement with data collected in the current study. Regarding R. pulmo, the general distribution pattern shown in the present study is consistent with that reported by Boero et al [15] and Leoni et al [93]. For P. noctiluca, one of the environmental variables with highest importance was salinity, which is in agreement with Piccinetti Manfrin and Piccinetti [94] and Canepa et al [30].…”
Section: Discussionsupporting
confidence: 93%
“…In the same study, the authors indicated that, by 2010, important impacts caused by this species had been reported by fishermen as a result of more frequent and intense blooms. Within our temporal dynamics analysis, a notable increase in R. pulmo records was observed from the year 2010 to 2013, with a considerable peak in 2012, agreeing also with the results shown in Leoni et al [93]. The spatial distribution observed in this study is also in agreement with Fuentes et al [102], showing the occurrence of this species along the entire Catalan coast, with the highest concentration in the central area around the Barcelona province.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Values represent the highest frequency of jellyfi sh occurrence in a given month, regardless of the number of reports received. Several authors have already used similar methods to present the results of macrozooplankton research [27,43,16,48,62,79,54].…”
Section: Data Collection / Prikupljanje Podatakamentioning
confidence: 99%
“…Rhizostoma pulmo ( S1 Fig ) is one of the first jellyfish species formally described in history [ 27 ], however, up to now, a complete description of its gastrovascular system is still missing, despite being a rather common jellyfish along the coasts of the Mediterranean Sea [ 28 , 29 ]. As part of a research on defining the phylogenetic pattern of the Rhizostoma genus, the morphology and functional anatomy of the species R .…”
Section: Introductionmentioning
confidence: 99%